HUBUNGAN STRES DENGAN MOTIVASI BELAJAR PADA MAHASISWA SEMESTER V PROGRAM STUDI ILMU KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Demolingo, Deyisi Pratiwi A.; Kalalo, Flora; Katuuk, Mario E. (JURNAL KEPERAWATAN, 2018)
Abstract : The motivation to study can influenced by stress and the same condition was on thecontrary stress it can affect the motivation to study but stressful which could be more profitablemanaged well it could be an encouragement to the motivation to study Purpose of this researchis to know the Relationship between Stress and Learning Motivation of the 5th semesterstudents of Nursing Program, Faculty of Medicine, University of Sam Ratulangi Manado.Sample of 73 respondents using total sampling technique. Design the research in this researchis correlative analysis, using Cross Sectional approach and data collected from respondentsby using questionnaire sheet. Results showed there’s no Relationship between Stress andLearning Motivation of the 5th semester students of Nursing Program, Faculty of Medicine,University of Sam Ratulangi Manado with p value = 0,062. Conclusion there is noRelationship between Stress and Learning Motivation of the 5th semester students of NursingProgram, Faculty of Medicine, University of Sam Ratulangi Manado.Keywords: Stress, Learning MotivationAbstrak : Motivasi belajar bisa dapat dipengaruhi oleh stres begitupun sebaliknya stres dapatmempengaruhi motivasi belajar akan tetapi stres yang bisa dikelola dengan baik bisa menjadisuatu dorongan untuk motivasi belajar. Tujuan dalam penelitian ini adalah untuk mengetahuihubungan stres dengan motivasi belajar pada mahasiswa semester V di Program Studi IlmuKeperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado. Sampel sebanyak 73responden dengan menggunakan teknik total sampling. Desain Penelitian dalam penelitian iniyaitu analisis korelatif, dengan menggunakan pendekatan Cross Sectional dan datadikumpulkan dari responden dengan menggunakan lembar kuesioner. Hasil Penelitianmenunjukan tidak adanya hubungan stres dengan motivasi belajar pada mahasiswa semester Vdi Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manadodengan nilai p= 0,062. Kesimpulan tidak terdapat hubungan stres dengan motivasi belajarsemester V di Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas SamRatulangi Manado.Kata Kunci : Stres, Motivasi Belajar.